Forward and Inverse Dynamics of the Biped PASIBOT. (28th July 2014) - Corral, Eduardo; Meneses, Jesús; Castejón, Cristina; García-Prada, Juan Carlos
This article addresses the supporting foot slippage of the biped robot PASIBOT and develops its forward and inverse dynamics for simple and double support phases. To address the slippage phenomenon, we consider an additional degree of freedom at the supporting foot and also distinguish between static and kinetic friction conditions. The inverse and forward dynamics, accounting for support foot slippage, are encoded in MATLAB. The algorithm predicts the motion of the biped from the torque function given by the biped's sole motor. Thus, the algorithm becomes an indispensable tool for studying transient states of the biped (for example, the torques required for starting and braking), as well as defining the conditions that prevent or control slippage. Since the developed code is parametric, its output can greatly assist in the design, optimization and control of PASIBOT and similar biped robots. The topology, kinematics and inverse dynamics of the one-degree-of-freedom biped PASIBOT have been previously described, but without regard to slippage between the supporting foot and the ground.